2017
DOI: 10.3389/fneur.2017.00093
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Retinal Nerve Fiber Layer Thickness and the Evolution of Cognitive Performance in an Elderly Population

Abstract: Retinal nerve fiber layer (RNFL) thickness is reduced in Alzheimer’s patients. However, whether it is associated with early evolution of cognitive function is unknown. Within 427 participants from the Three-City-Alienor longitudinal population-based cohort, we explored the relationship between peripapillary RNFL thicknesses and the evolution of cognitive performance. RNFL was assessed at baseline by spectral domain optical coherence tomography; cognitive performances were assessed at baseline and at 2 years, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…Moreover, many authors claim that the retina can be considered as a window to the brain, the eye being an extension to the central nervous system. 52,53 Future work will investigate the evolution of cognitive performances through subsequent waves of the 3C study in relation to baseline MPOD and plasma LþZ concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many authors claim that the retina can be considered as a window to the brain, the eye being an extension to the central nervous system. 52,53 Future work will investigate the evolution of cognitive performances through subsequent waves of the 3C study in relation to baseline MPOD and plasma LþZ concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that patients with stroke have reduced RNFL thickness than have healthy controls ( 33 , 34 ), an association between the reduced thickness and visual function has not been reported yet. The pRNFL, which contains axons ( 42 ), has been reported to play an important role in vision because of its proximity to the optic nerve (cranial nerve II). The association between pRNFL thickness and VA suggests that insult to the pRNFL thickness have a significant effect on the VA of RSSI patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a debate in the literature related to whether disease stage should be assessed using vision data from the worse eye or better eye. While disease stage in the better eye has traditionally been used as a clinical assessment of visual function and quality of life 35 , 36 , the most affected eye or worse eye has been implicated in structural changes in the brain 26 , cognitive impairments 37 and even quality of life measures 38 . In this study, while it is anticipated that data from the better eye will be most relevant, data from both eyes were considered.…”
Section: Methodsmentioning
confidence: 99%